Correlations of SPT and DCPT data for sandy soils in Ghana - K.O. Opuni; S.O. Nyako; B. Ofosu; F.A. Mensah; K. Sarpong (International Association of Lowland Technology, 2017)
Standard penetration test (SPT) is the most commonly used insitu test for site investigations and foundation design with wellestablished correlations between the SPT and soil properties. However for simple structures in developing countries the SPT is considered uneconomical. The dynamic cone penetration test (DCPT) is a rapid inexpensive field test that can be used to determine the material properties of soils. In this study the two in-situ tests are carried out side by side in sandy soils and a correlation of the DCPT results with SPT results and allowable bearing capacity investigated. The results indicate that the relation between the results of the two in-situ tests is linear for sandy soils. The local DCPT – SPT and DCPT – allowable bearing capacity correlations obtained compare well with those in literature.